A redescription of the monotypic felt scale insect genus Pedroniopsis Green (Hemiptera: Coccomorpha: Eriococcidae) from India and Burma - Hodgson, Chris J.; Williams, Douglas J. (Zootaxa, 2016)
Here we redescribe the felt scale genus Pedroniopsis Green and its type species Pedroniopsis beesoni Green for the first time since it was described 90 years ago. We consider that the genus belongs to the family Eriococcidae as presently understood but realise that the family may not be monophyletic. The species was collected in crevices and pits on the bark of Shorea robusta (Dipterocarpaceae) from Odisha State, India, which is its only known locality in India. We also record the species from Burma (Myanmar) for the first time living in galls on Dipterocarpus tuberculatus (Dipterocarpaceae) and, therefore, the species may have a wider distribution but has not been observed because of its cryptic habit. The adult females of the genus and species have some unusual features such as truncate-conical marginal and dorsal setae that are mostly bifid at the tip. We suggest that the genus may be similar in some respects to the genus Sangicoccus Reyne known from farther east in southern Asia.